Denitrification: an ecosystem service provided by salt marshes - Sousa, Ana I. (2019)
We hypothesized that denitrification rates, as an N removal process, would be enhanced in salt marsh rhizosediments as compared to sediments without vegetation (bare mudflats). Denitrification rates (measured by the 15N-isotope pairing technique), potential nitrification, and nutrient fluxes were seasonally quantified in a Spartina maritima salt marsh and in adjacent bare mudflats. Potential nitrification rates were significantly higher in autumn and winter, but there were no significant differences between the bare mudflats and S. maritima vegetated sediment. Seasonally, denitrification rates in vegetated sediments under dark conditions were significantly higher in winter (676 ± 497 µmol N2 m−2 h−1, mean ± SD), whereas bare mudflats showed a maximum rate of 151 ± 24 µmol N2 m−2 h−1 in summer. The high denitrification rates recorded in winter may be due to many abiotic and biotic factors, namely higher potential nitrification and nitrate availability in the water column, lower competition for nitrogen within the sediment, and less competition between plants, microphytobenthos, and nitrifiers, especially in dark conditions. Hence, during winter, there was a higher contribution of S. maritima marshes to N removal through denitrification, highlighting the role of the marshes in this ecosystem service. As a whole, considering the seasonal variations of the studied processes, it cannot be concluded whether or not annual de nitrification was significantly different between the vegetated sediment and the bare mudflats.